Triathlon 2.0 data-driven performance training - Vance, Jim 1976- (Champaign, IL Human Kinetics, 2016)
Examines the sport's most popular devices including cycling power meters, GPS trackers, and heart rate monitors. Learn to capture the most accurate readings, learn what they mean, and, just as important, what they don't mean. Learn to translate your data into a program based on your performance needs and triathlon goals.
Part I. Triathlon training technology -- Cycling technology -- Running technology -- Swimming technology -- Part II. Planning your training -- Assessing triathlon fitness -- Planning the training year -- Part III. High-tech periodization -- Training analysis software -- Stress-based periodization -- Transition and preparation phases -- Base phase -- Build phase -- Tapering and peaking -- Part IV. Race analysis for winning results -- Preface preparations -- In-race monitoring -- Postrace analysis -- Postseason analysis.
Includes bibliographical references and index.
Keywords: Triathlon -- Training